A CRITICAL GENRE-BASED APPROACH TO TEACHING ACADEMIC WRITING AND BUILDING CHARACTER : A Case Study with Tertiary EFL Students in Pontianak Indonesia - Aunurrahman, - (2018)
Academic writing serves as a medium for tertiary students to learn the knowledge base of their discipline. It is also a medium that can develop the students' critical thinking (Swartz & McGuinness, 2014) and character (Lickona, 1999a). This case study was designed to find out (1) whether a critical genre-based approach (CGBA) can help develop academic writing, critical thinking, and character of the tertiary students of a private university in Pontianak, West Kalimantan, Indonesia and (2) in what ways a critical genre-based approach can help develop the aforementioned aspects. The study involved 37 first-year regular class students of the English education programme. The study was conducted in the second semester for 19 meetings. Introductory sessions to critical thinking, character, systemic functional linguistics (SFL), systemic functional linguistics genre-based approach (SFL GBA), and systemic functional grammar (SFG) were conducted, followed by the implementation of the systemic functional linguistic genre-based approach (SFL GBA) teaching stages in 2 cycles. The data were collected from participant observation field notes, students' responses to the open-ended questionnaires, transcripts of the students' interviews, and documentation of the students' texts. The data were analysed using the thematic analysis. The students' texts were analysed by using the systemic functional grammar. After the completion of the data analyses, a data triangulation was conducted. The results show that a critical genre-based approach can help develop the students' academic writing, critical thinking, and character where the study applied teaching stages of SFL GBA, explicit guidance, group work, and a recursive process of academic writing that includes the lecturer and peer feedback. The applications of the group work and peer feedback in the practices enabled the students to work as a team as they built a sense of diligence, honesty, responsibility, care and respect to reach a mutual goal, that is, good academic texts. It is also supported by the results of the analyses of the students' texts using the systemic functional grammar that show a good development of the students' academic writing, critical thinking, and character as reflected in the students' control of the schematic structure of an exposition genre with its linguistic features, followed by their control of the intellectual standards and the ethics of academic writing that can indicate a good practice of the character values, e.g. honesty, fairness, and respect. The findings suggest that the critical genre-based approach should be applied to tertiary students across the curriculum in different contexts in Indonesia to prepare the students to work on academic assignments. Another suggestion is, explicit teaching should be performed to allow the students to achieve a relatively similar understanding and competence in academic writing.;--Menulis teks akademik merupakan medium untuk mahasiswa belajar. Menulis teks akademik juga merupakan medium yang dapat mengembangkan kemampuan berpikir kritis (Swartz & McGuinness, 2014) dan karakter mahasiswa (Lickona, 1999a). Studi kasus ini bertujuan untuk mengetahui (1) apakah critical genre-based approach dapat membantu mengembangkan penulisan teks akademik, pemikiran kritis, dan karakter mahasiswa pendidikan Bahasa Inggris di suatu perguruan tinggi swasta di Pontianak, Kalimantan Barat, Indonesia dan (2) bagaimana critical genre-based approach dapat mengembangkan aspek-aspek tersebut. Studi ini melibatkan 37 mahasiswa kelas reguler dari program studi pendidikan Bahasa Inggris. Studi ini dilakukan di semester kedua sebanyak 19 pertemuan. Sesi perkenalan mengenai pemikiran kritis, karakter, linguistik fungsional sistemik, pendekatan berbasis genre, dan tata bahasa fungsional sistemik diadakan, dilanjutkan dengan implementasi pengajaran bertahap pendekatan berbasis genre dalam 2 siklus. Pengumpulan data dilakukan dengan menggunakan catatan observasi partisipasi, respon mahasiswa terhadap kuesioner terbuka, transkrip interviu dengan mahasiswa, dan dokumentasi tulisan mahasiswa. Selesai dengan pengumpulan data, analisis tematik dilakukan terhadap data tersebut. Teks mahasiswa dianalisis menggunakan tata bahasa fungsional sistemik. Triangulasi data dilakukan kemudian. Hasil analisis menunjukkan bahwa pendekatan ini dapat membantu mengembangkan penulisan teks akademik, pemikiran kritis, dan karakter mahasiswa melalui tahapan pengajaran pendekatan berbasis genre, pengajaran eksplisit, kerja kelompok, dan proses rekursif menulis ilmiah yang termasuk umpan balik dosen and teman sejawat. Penerapan kerja kelompok dan umpan balik teman sejawat dalam prakteknya memungkinkan mahasiswa untuk bekerja dalam satu tim dimana mereka membangun nilai ketekunan, kejujuran, tanggung jawab, peduli dan hormat untuk meraih satu tujuan yang sama, yaitu teks akademik yang baik. Temuan ini didukung dari hasil analisis teks mahasiswa menggunakan tata bahasa fungsional sistemik yang dapat menunjukkan perkembangan yang baik akan kemampuan mahasiswa dalam menulis teks akademik, berpikir kritis, dan karakter. Hal ini terrefleksi dari kontrol mahasiswa akan struktur skematik dan fitur linguistik genre eksposisi yang diikuti dengan kontrol mereka akan standar intellektual atau disposisi dan etika menulis teks akademik yang dapat mengindikasikan praktek yang baik akan nilai-nilai karakter seperti kejujuran, keadilan, dan hormat. Temuan-temuan ini menyarankan bahwa critical genre-based approach harus diaplikasikan kepada mahasiswa perguruan tinggi dengan berbagai disiplin di konteks-konteks yang berbeda di Indonesia untuk mempersiapkan mereka mengerjakan tugas akademik. Saran lainnya adalah pengajaran eksplisit harus dilakukan kepada mahasiswa untuk memungkinkan mereka meraih pemahaman dan kompetensi menulis teks akademik yang relatif sama.